Library Automation: a Case Study of Barr. Balasaheb Khardekar Library, Shivaji University, Kolhapur - Birje, S. R.; Khamkar, R. D.; Gurav, D. S.; Mahajan, S. D. (Journal of Information and Knowledge, 2013)
Library automation is becoming a ubiquitous activity that is being taken up by most of the libraries of educational institutes of higher learning over the globe. However, when it comes to automation of the library of a traditional University in the backdrop of the rural ambience and with the weak IT base both in terms of skilled human resource and services, it poses many challenges. The present paper narrates the various dimensions of the implementation of the Library Automation project in any University Library in general and conventional University Libraries in particular. A case study of the automation of the Barrister Balasaheb Kharderkar Library of Shivaji University is detailed in the present communication to showcase some of the challenges and the strategies required to overcome them in a rural cum semi-urban environment. The paper discusses the phase wise development of the automation process that comprises of retro conversion, barcode code ID generation, member id generation, and house keeping operations. The authors intend to share their experiences may be useful to other professionals.